The myth of monophagy in Paralobesia (Lepidoptera: Tortricidae)? A new species feeding on Cypripedium reginae (Orchidaceae) - Royals, Hanna R.; Landry, Jean-François; Gilligan, Todd M. (Zootaxa, 2018)
The genus Paralobesia Obraztsov, 1953 is found primarily in eastern North America and consists of 18 described and several undescribed species. Prior to 1900, all North American Paralobesia were assumed to be P. viteana (Clemens). However, rearing experiments by William Kearfott in the early 1900s suggested that species of Paralobesia were monophagous and could be separated by host. Recently, a species of Paralobesia was reared from showy lady’s slipper, Cypripedium reginae Walter (Orchidaceae), during a study of two populations of this orchid in eastern Ontario and southwestern Québec. Although originally assumed to be P. cypripediana (Forbes), which was described from specimens reared from Cypripedium in Manitoba, DNA barcode data and genital morphology confirmed that this was a new species similar to P. cypripediana and P. monotropana (Heinrich). Herein, we describe P. marilynae, sp. n., and provide specifics of its discovery and life history. Rearing records indicate that Paralobesia can span the range from strictly monophagous to polyphagous, even for very similar species with similar feeding habits, and that host records should be combined with morphological and molecular data when circumscribing species in this genus. This work is part of a complete systematic revision of Paralobesia currently in progress.